The Reality of Entrepreneurial Marketing in the Palestinaian insurance companies at Gaza Strip - Abu Alsoud, Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to identify the reality of Entrepreneurial Marketing, applying on the Palestinaian insurance companies in Gaza Strip. The descriptive analytical method was used applying the comprehensive inventory method. The size of community 84 individuals working at palestinian insurance companies. The questionnaire was used as main tool for collecting data. Among the most important results of the Research findings ahigh level Entrepreneurial Marketing at insurance companies in gaza strip, the most important recommendations is the necessity of establshing adepartment for Entrepreneurial Marketing at palestinian insurance companies.